The response of soil physicochemical properties to tillage and soil fertility resources in Central Highlands of Kenya - Kiboi, Milka N.; Ngetich, Felix K.; Muriuki, Anne; Adamtey, Noah; Mugendi, Daniel (Italian Journal of Agronomy, 2020)
To attain agricultural sustainability, use of soil resources and tillage requires equal consideration for chemical and physical components of soil fertility. We assessed responses of selected soil physical and chemical properties to tillage and soil fertility amending resources. The study was carried out in Meru South and Kandara sub-counties located in the Central Highlands of Kenya for four cropping seasons. The experimental design was split-plot with tillage as the main factor - conventional (D15) - and minimum (D0) tillage and soil fertility resources (SFR) as sub-factors - mineral fertilizer (F), crop residues + fertilizer (RF), residues + fertilizer + animal manure (RFM), residues + Tithonia diversifolia + manure (RTiM), residues + Tithonia diversifolia + phosphate rock (Minjingu) (RTiP), residues + manure + legume intercrop (RML) and control (no input). Compared with control, aggregate stability was significantly higher on average under SFRs with sole organics by 19% in Meru South. Total N and available P were higher under integration of fertilizer and organics in both sites. Calcium increased under sole organic or integration with fertilizer in Meru South and under sole organics in Kandara. Magnesium significantly increased under all SFRs compared with control in Kandara. Soil organic carbon significantly (P=0.02) increased under D0 by 6% compared to D15 in 0-5 cm depth in Kandara. Application of RTiM had the highest SOC in all depths’ at Meru South. SOC significantly increased under RTiP and RML by 11% in 0-5 cm depth and under RML by 13% in 5-10 cm depth at Kandara. Mineral-N (NO3–-N and NH4+-N) was higher under D0 at planting compared with D15 in Meru South. In Kandara, NO3–-N and NH4+-N were significantly higher by 17% and 30%, respectively under D0 compared with D15 at planting during SR16 season. Higher mineral N was recorded under F application on the 30th and 45th days in both sites. The highest mineral-N content was on the 45th day after planting during SR16 season and on the 30th day during LR17 season at Meru South. In Kandara, NO3–-N and NH4+-N were highest on the 45th day and 30th day, respectively, during SR16 season. During LR17 season, mineral-N was highest on the 30th day in Kandara. The study highlights that minimal soil disturbance and organic inputs use or integration with fertilizers are feasible alternatives for improving soil fertility in the Nitisols of Central Highlands of Kenya. Highlights - Application of sole organic inputs or in combination with mineral fertilizer enhances soil chemical properties - Minimum tillage and use of organic soil inputs increases soil organic carbon - Different tillage practices in combination with soil inputs increases soil mineral nitrogen - Minimum tillage, use of sole organic inputs and/or integration with fertilizers improves soil fertility in clayey soil